Male aging as a causative factor of detrimental changes in human conventional semen parameters and sperm DNA integrity. (4th December 2020) - Gill, Kamil; Jakubik-Uljasz, Joanna; Rosiak-Gill, Aleksandra; Grabowska, Marta; Matuszewski, Marcin; Piasecka, Malgorzata
Abstract: The effect of male aging on fertility potential is controversial and difficult to predict. The aim of our study was to determine the associations between age, basic semen parameters, and sperm DNA fragmentation (SDF). Comparison of four age-dependent groups (men ≤29 years, 30–35 years, 36–40 years, and >40 years) revealed a significant fall in the basic semen characteristics and sperm genomic integrity with age. Receiver operating characteristic (ROC) analysis confirmed that men >29 years had lower semen quality. In the group of men >29 years, the prevalence of men with abnormal semen parameters was higher, and these men had over a threefold higher odds ratio (OR) for abnormal semen parameters. Next, ROC analysis revealed that a threshold of 18% SDF was optimal for discriminating between men with normal and abnormal standard semen parameters. The prevalence of men with >18% SDF was higher in the group of men >29 years than in men ≤29 years. Older men had an almost twofold higher risk for >18% SDF than younger men. Our results suggest that age >29 years may be a causative factor of detrimental changes in semen quality, which may raise the risk for disorders of male fertility potential.